Pengaruh Pengembangan Karyawan terhadap Kinerja Karyawan dengan Kompetensi sebagai variabel intervening pada KSP Duta Mandiri Makmur Kediri - Sulistien Sulistien; IGG Heru Marwanto; Budi Rahayu; Nur Laely (Fakultas Ekonomi Universitas Kadiri, 2022)
The success of a company's performance is determined by the quality of employee performance. Employees as the main asset that determines the success or failure of the company are required to achieve the company's vision and mission by improving performance as an indicator in achieving company success, therefore the company seeks to improve competence according to job requirements in achieving good performance. The research objective was to identify and analyze the effect of employee development on employee performance at KSP Duta Mandiri Makmur Kediri. Makmur Kediri, to find out and analyze the effect of employee development on employee performance through competence as an intervening variable at KSP Duta Mandiri Makmur Kediri. The type of research is quantitative, the approach used is a survey approach, the nature of the research is explanatory research. This research was conducted at KSP Duta Mandiri Makmur with the address Jl. gg. Slamet No. 08 Pare District, Kediri Regency. The results obtained are career development has no effect on performance, career development has an effect on employee competence, awareness that with fast developments, competence has an effect on performance, 4. Competence mediates the effect of career development on employee performance.